Geological reasons causing rapid rate decline. A case study of Field T, Russia; IOP Conference Series: Earth and Environmental Science; Vol. 24 : Scientific and Technical Challenges in the Well Drilling Progress, 24–27 November 2014, Tomsk, Russia - Kuzmin S. (2015, 2015)
Title screen